2003
DOI: 10.2139/ssrn.630121
|View full text |Cite
|
Sign up to set email alerts
|

Impact of School Finance Reform on Resource Equalization and Academic Performance: Evidence from Michigan

Abstract: The state of Michigan radically altered its school finance system in 1994. This was a legislature-led reform that took place somewhat unexpectedly and without the intervention of any courts. The new plan, called Proposal A, significantly increased state aid to the lowest spending districts. I investigate the impact of Proposal A on distribution of resources and educational outcomes in Michigan. In the process this paper offers a first detailed look at the effectiveness of a legislature-led school finance refor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
(11 reference statements)
1
14
0
Order By: Relevance
“…We have replicated and extended the analyses of Papke (2005Papke ( , 2008 and Roy (2011). Later in this document, we use these results to extrapolate the amount of additional resources that it would take to upgrade Michigan's student achievement to the level of the U.S. average and to the level of exemplary states, as well as the resources it would take to reduce gaps between disadvantaged and non-disadvantaged students.…”
mentioning
confidence: 74%
“…We have replicated and extended the analyses of Papke (2005Papke ( , 2008 and Roy (2011). Later in this document, we use these results to extrapolate the amount of additional resources that it would take to upgrade Michigan's student achievement to the level of the U.S. average and to the level of exemplary states, as well as the resources it would take to reduce gaps between disadvantaged and non-disadvantaged students.…”
mentioning
confidence: 74%
“…Baker ( 2012 ) explains the evolution of assertions regarding the unimportance of money for improving student outcomes, pointing out that these assertions emanate in part from misrepresentations of the work of Coleman and colleagues in the 1960s, which found that school factors seemed less associated with student outcome differences than did family factors. This was not to suggest, however, that school factors 3 Roy ( 2011 ) published an analysis of the effects of Michigan's 1990s school fi nance reforms that led to a signifi cant leveling up for previously low-spending districts. Roy, whose analyses measure both whether the policy resulted in changes in funding and who was affected, found that the proposal "was quite successful in reducing interdistrict spending disparities.…”
Section: Money and School Finance Reformsmentioning
confidence: 99%
“…20 that these schools were relatively more concentrated in these districts -so that property values went up due to charter schools, and wealthier and more educated households relocated to take advantage of these schools. However, the opposite is true in Michigan (see Roy 2011). The lowest spending groups (Groups 1 and 2) are predominantly rural, while charter schools in Michigan mostly serve urban city children and are located in the high spending districts.…”
Section: Examining the Role Of Charter Schools As A Potential Confounmentioning
confidence: 99%
“…Over time, the gap in spending was significantly reduced. Also, there is considerable evidence (Papke, 2005;Papke, 2008;Roy, 2011) that the reform led to significant gains in academic performance in the lowest spending districts and the gap in educational outcomes between the highest and lowest 1 spending districts narrowed. This relative equalization sets the stage for studying the impacts on socioeconomic segregation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation